The power of storytelling is not black and white: a case study unpacking the tensions of storytelling as a pedagogy for racial justice education - Hobson, Tess (Kansas State University, 2021)
Storytelling is a powerful tool to be utilized within racial justice education. It humanizes our experiences, promotes empathy, and allows us to connect across difference. Existing literature illustrates the influence of storytelling being rooted in marginalized populations and its ability to transcend cultural contexts (Banks-Wallace, 1998; Bell, 2009; Chin & Rudelius-Palmer, 2010; Delgado, 1989; Delgado Bernal et al., 2012; Pyke, 2010; Solórzano & Yosso, 2002). What is lacking from existing literature is narrative accounts of racially diverse college students’ experiences with storytelling as a pedagogical approach in social justice, and more specifically, racial justice education contexts. Additionally, although some literature exists on how storytelling can disrupt the system of whiteness, there is a lack of narrative accounts of how whiteness can disrupt storytelling as a pedagogy. In this instrumental case study, I utilize a Critical Whiteness Studies (CWS) theoretical framework to highlight the narratives of five, racially diverse, undergraduate college students about their experiences with storytelling as a teaching tool for racial justice education within an intercultural leadership course. Through interview and document analysis data, I identified three overarching themes that illustrate how students of diverse racial backgrounds perceived storytelling as a teaching tool for racial justice education including: 1) Storytelling is a Powerful and Empowering Teaching Tool, 2) Hesitancy in Being the Storyteller, and 3) The Classroom Door is not a Whiteness Gatekeeper. Results from this study can increase our understanding of storytelling as a pedagogy for racial justice education and the ways in which the pervasive nature of whiteness manifests in storytelling communities. While the power of storytelling was reflected in participants’ experiences, the study also raises our consciousness about the considerations educators should make in implementing a storytelling pedagogy in predominantly white classroom settings. Based on these findings I provide implications for research and practice.
Keywords: Storytelling; Social justice education; Racial justice education; Critical whiteness studies